Preliminary Study on the Security Domain Transformation of SMS Platform - Siwei Huang; Hong Li (Dianxin kexue)
Taking the protection of information security as the focus,the technical level in the security protection of information system,the partition of security domain and boundary integration transformation were analyzed and discussed.China Telecom SMS platform was selected as a typical case,and the security domain transformation of systems as message couters and gateways were researched and analyzed.The conclusion could provide good guidance for other service platform of information security,business continuity.